Enhancing safety climate through occupational safety and health practices mediating by management commitment in the hospital setting - Ghimire, Subash; Mishra, Anjay Kumar; Bhaumik, Amiya (International Journal of Occupational Safety and Health, 2025)
Introduction: Hospitals encounter problems sustaining a favorable safety climate due to their inherent complexity and ongoing needs. This study examines the relationship between occupational safety and health (OSH) practices and safety climates mediated by management commitment in hospitals. Methods: Data was acquired from 400 healthcare professionals in hospitals in Kathmandu using a structured survey utilizing a cross-sectional quantitative approach. A stratified random sampling technique was employed to ensure representation across different healthcare professional roles in the hospital. The data was collected from February 15, 2023, to April 15, 2023. The complex relationships between OSH practices, management commitment, and safety climate were evaluated by Structural Equation Modeling (SEM). Results: The result findings reveal that the safety climate is significantly influenced by OSH practices, as evidenced by a standardized regression weight of 0.75. This result suggests that better OSH practices result in enhanced safety perceptions. Although management commitment also serves as a critical mediating factor, its effect size is lower, indicating that it remains a critical factor despite its less pronounced impact than direct OSH interventions. The safety climate is primarily driven by OSH practices, as confirmed by the validated framework, and their effectiveness is further enhanced by management commitment. The study's uniqueness was that it inspected the mediating role management commitment plays in the relationship between OSH practices and safety climate. Conclusion: Hospitals should enhance OSH practices and promote management commitment to improving the safety climate. Future studies should examine additional mediators, use longitudinal studies, and analyze several healthcare settings to further investigate safety climate dynamics.